PROTECTIVE ROLE OF HUMAN BREAST MILK AGAINST NECROTIZING ENTEROCOLITIS IN PRETERM INFANTS - Putri, Dyah Arista; Patandianan, Firdaus Kamma; Latifa, Nindy Citra; Ramadhania, Yasmin Najla; Rofilah, Alita Khainur; Maharani, Baiq Syarifaturrayyan; Yassa, I Wayan Radityakara Wirasena; Arigi, Lalu Ahmad Gamal (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
Necrotizing enterocolitis (NEC) is a life-threatening gastrointestinal disease that predominantly affects preterm infants, with high rates of morbidity and mortality. Human breast milk (HBM) has long been recognized as the most effective nutritional intervention for preventing NEC due to its unique bioactive components such as immunoglobulins, lactoferrin, glutamine, vitamins, and human milk oligosaccharides (HMOs), which act through mechanisms including strengthening the intestinal barrier, modulating immune responses, and regulating the gut microbiota. This narrative review aims to synthesize recent evidence on the protective role of HBM against NEC, with particular emphasis on the function of HMOs, probiotics, and complementary nutritional interventions designed to replicate or enhance HBM’s bioactivity. The methods applied in this review followed a narrative literature search in PubMed, Scopus, and Google Scholar for studies published between 2015 and 2025 on the effects of breastfeeding on NEC risk in preterm infants, using predefined eligibility criteria. The findings indicate that HBM significantly reduces NEC incidence, while supplemental interventions such as prebiotics and probiotics may serve as complementary strategies, particularly when the availability of mother’s own milk is limited. Overall, HBM remains the primary protective factor against NEC, and optimizing its provision in neonatal care is critical for improving outcomes among preterm infants.